Aportaciones técnicas al análisis psicológico retrospectivo en el Ecuador - Poveda, Edgar R. (2021)
In the field of criminology, when faced with doubtful deaths, professionals competent in matter of criminal investigation are unable to issue an unequivocal verdict about the factors surrounding the death of a person, because they do not have abundant, evident and conclusive information that allows them to do so. Thus, the figure Psychological Autopsy (AP) technique as an application tool aimed at obtaining useful and complementary information for the criminal investigation in this type of situation (Núñez de Arco, 2005). The AP concept began to be used from the 1950s to define a technique that facilitates, from a retrospective approach, the reconstruction of the most relevant previous or recent aspects of the life of the deceased person (PF), in particular those that may be related to his death, using the following sources of information or analysis perspectives: sociodemographic characteristics.